In vivo knockdown of hippocampal miR‐132 expression impairs memory acquisition of trace fear conditioning. Issue 7 (29th April 2013) - Wang, Ruo‐Yu; Phang, Rui‐Zhe; Hsu, Pei‐Hsuan; Wang, Wei‐Hua; Huang, Hsien‐Ting; Liu, Ingrid Y
ABSTRACT MicroRNA‐132 (miR‐132) has been demonstrated to affect multiple neuronal functions, including dendritic growth and spinogenesis in cultured neurons and brain slices, as well as learning behavior of animals. However, its role in acquisition of temporal‐associated memory remains unclear. In this study, we demonstrated that the mature miR‐132 level in mouse hippocampus was significantly increased at 30 min after trace fear conditioning, a type of temporal‐associated learning, and returned to baseline values in 2 h. We then knocked down miR‐132 expression in vivo by infusing a lentivector expressing anti‐miR‐132 hairpin RNA into the third ventricle near the anterior hippocampi such RNA diffused laterally to both hippocampal formations, later confirmed by histological analysis. This approach successfully reduced hippocampal miR‐132 expression in both naïve and trace fear conditioned groups, and impaired acquisition of trace fear memory in mice. To our knowledge, this result is the first demonstration of change in temporal learning behavior by reducing microRNA (miRNA) level specifically in the hippocampal region. © 2013 Wiley Periodicals, Inc.